(untitled) (Baghdad Science Journal, 2007)
Adsorption of Chlorophenol compounds in aqueous solution on Iraqi siliceouns rocks powder have been investigated. UV technique has been used to determine the adsorption isotherms. The results showed that the adsorption isotherms obeyed Freundlich adsorption equation. The adsorption was endothermic process, increasing temperature leads to increasing adsorption. H, S, G were calculated. The results showed that the adsorption increases with increasing acidity of solutions.